Policaptil Gel Retard® significantly reduces body mass index and hyperinsulinism and may decrease the risk of type 2 diabetes mellitus (T2DM) in obese children and adolescents with family history of obesity and T2DM - Stagi, Stefano (Ital J Pediatr, 2015)
BACKGROUND: Treatments for childhood obesity are critically needed because of the risk of developing co-morbidities, although the interventions are frequently time-consuming, frustrating, difficult, and expensive. PATIENTS AND METHODS: We conducted a longitudinal, randomised, clinical study, based on a per protocol analysis, on 133 obese children and adolescents (n = 69 males and 64 females; median age, 11.3 years) with family history of obesity and type 2 diabetes mellitus (T2DM). The patients were divided into three arms: Arm A (n = 53 patients), Arm B (n = 45 patients), and Arm C (n = 35 patients) patients were treated with a low-glycaemic-index (LGI) diet and Policaptil Gel Retard®, only a LGI diet, or only an energy-restricted diet (ERD), respectively. The homeostasis model assessment of insulin resistance (HOMA-IR) and the Matsuda, insulinogenic and disposition indexes were calculated at T(0) and after 1 year (T(1)). RESULTS: At T(1), the BMI-SD scores were significantly reduced from 2.32 to 1.80 (p < 0.0001) in Arm A and from 2.23 to 1.99 (p < 0.05) in Arm B. Acanthosis nigricans was significantly reduced in Arm A (13.2% to 5.6%; p < 0.05), and glycosylated-haemoglobin levels were significantly reduced in Arms A (p < 0.005). The percentage of glucose-metabolism abnormalities was reduced, although not significantly. However, the HOMA-IR index was significantly reduced in Arms A (p < 0.0001) and B (p < 0.05), with Arm A showing a significant reduction in the insulinogenic index (p < 0.05). Finally, the disposition index was significantly improved in Arms A (p < 0.0001) and B (p < 0.05). CONCLUSIONS: A LGI diet, particularly associated with the use of Policaptil Gel Retard®, may reduce weight gain and ameliorate the metabolic syndrome and insulin-resistance parameters in obese children and adolescents with family history of obesity and T2DM.